Radical Fashion Exercises : A workbook of modes and methods - Gardner, Laura, ....-; Mohajer va Pesaran, Daphne, ....- (Amsterdam : Valiz, 2023)
Over 100 tried and tested exercises to expand how we look at fashion, how we are part of its system and how we can practice fashion otherwise--for students of all ages and teachers of all disciplines. Radical Fashion Exercises assembles methods for learning and practicing fashion in meaningful, radical and responsible ways. The book is an inspiring tool for design students, designers, writers and practitioners of diverse disciplines to challenge fashion as a commodity and polluting structure in these times of uncertainty and upheaval.
Keywords: Design; Fashion